Study of (W/Z)H production and Higgs boson couplings using H→WW∗ decays with the ATLAS detector - Aad, G. (2015)
A search for Higgs boson production in association with a W or Z boson, in the H→WW∗ decay channel, is performed with a data sample collected with the ATLAS detector at the LHC in proton-proton collisions at centre-of-mass energies √ s = 7 TeV and 8 TeV, corresponding to integrated luminosities of 4.5 fb−1 and 20.3 fb−1 , respectively. The W H production mode is studied in two-lepton and three-lepton final states, while twolepton and four-lepton final states are used to search for the ZH production mode. The observed significance, for the combined W H and ZH production, is 2.5 standard deviations while a significance of 0.9 standard deviations is expected in the Standard Model Higgs boson hypothesis. The ratio of the combined W H and ZH signal yield to the Standard Model expectation, µV H, is found to be µV H = 3.0 +1.3 −1.1 (stat.) +1.0 −0.7 (sys.) for the Higgs boson mass of 125.36 GeV. The W H and ZH production modes are also combined with the gluon fusion and vector boson fusion production modes studied in the H → WW∗ → `ν`ν decay channel, resulting in an overall observed significance of 6.5 standard deviations and µggF+VBF+VH = 1.16+0.16 −0.15(stat.) +0.18 −0.15(sys.). The results are interpreted in terms of scaling factors of the Higgs boson couplings to vector bosons (κV ) and fermions (κF ); the combined results are: |κV | = 1.06+0.10 −0.10, |κF | = 0.85+0.26 −0.20